Effect of in-situ Fe doping on the visible light photoelectrochemical activity of TiO2 nanorods - Nam Trung Tran; Thi Minh Huong Pham; Tan Lam Nguyen (Vietnam Journal of Science, Technology and Engineering, 2022)
Considering its superior photocatalytic activity and excellent chemical stability, titanium dioxide (TiO2) is an excellent candidate for photoelectrochemical (PEC) hydrogen production. Besides, many challenges exist ahead of improving the photoresponse of TiO2 to visible light while maintaining high photocatalytic activity. Herein, the authors report recent efforts to improve the visible light PEC activity of TiO2 nanorods by in-situ doping with various iron (Fe) concentrations using a hydrothermal method. The influences of Fe doping concentrations on the morphological and structural properties of TiO2 nanorods were investigated by using scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy. Furthermore, this work demonstrates that Fe doping could improve the PEC activity of TiO2 nanorods under visible light irradiation. The authors achieve a remarkable enhancement in the photocurrent density, as high as 2.9 mA/cm2 at an applied voltage of 0.5 V, for the sample synthesised with an Fe doping concentration of 10 mM. These results reveal that Fe-doped TiO2 nanorods can serve as ideal materials for PEC applications.